Chimamanda Adichie, Mia Couto and their struggle against gender expectations - Amante, Susana (Revista Estudos Feministas, 2022)
In A coisa à volta do teu Pescoço, the Nigerian writer Chimamanda Adichie brings life and voice to various female characters, but, in a convenience sampling, we will stick to those in the short stories “Cela Um” and “A Historiadora Obstinada”. Gender issues, in another part of Africa, are dealt with by Mia Couto, a staunch feminist. It is in the quest for a new direction ensuring women's rights that we will analyse the feminine representativeness in selected short stories in Estórias Abensonhadas, such as “Esteira do Parto”, “O Perfume”, “Os infelizes cálculos da felicidade”, “Joãotónio, no enquanto” and “Os olhos fechados do diabo do advogado”. Taking these authors as a reference, we will try to analyse 1. the ways in which women are represented in the narratives under study and 2. how much more (un)happy female characters become when they do not feel the weight of gender expectations.